Gianni Pettena : 1966-2021. - Cerizza, Luca; Pettena, Gianni; Obrist, Hans Ulrich (Milano : Mousse Publishing, 2020)
Gianni Pettena (born 1940, Bolzano, Italy) was a central figure in research regarding the boundary between architecture and art in the later 1960s - a movement Germano Celant dubbed "radical architecture." Together with the Florentine groups Archizoom, Superstudio, and UFO, and Turinese groups like the Gruppo Strum, Pettena helped expand and redefine the limits of what could be described as architecture, making a fundamental contribution to the ferment that animated, at an international level, city planning debates in those years. Independently of his fellow radicals in Florence, Pettena took an anarchic and ironic attitude toward authority, whether exercised in politics, progress, or planning. Through an extraordinary variety of means, including installation, performance, photography, video, and design, he has remained "on strike out of his love of architecture" for more than fifty years. Rather than practice the discipline, he has chosen to challenge it through the language of art, critical and expository writing, and the medium of teaching. Within a practice filled with implications, attention to a respectful relationship with nature and its resources has been a constant characteristic of his work, and remains a crucial lesson in the context of the current environmental crisis.
Text in Italian and English.
kunstcatalogus
Keywords: Pettena, Gianni; Radical architecture; Art and architecture